Freedom under the Word : Karl Barth's theological exegesis - Rhodes, Ben, 1983-; Westerholm, Martin (Grand Rapids,MI Baker Academic, 2019)
"Renowned scholars offer critical engagements with Karl Barth's exegesis of Christian Scripture and explore its implications for contemporary hermeneutics and biblical interpretation. Focusing on rare texts from the Barth corpus, Freedom Under the Word considers the legacy and potential of Barth's theology by presenting a wide-ranging engagement with and assessment of Barth's theological exegesis. The volume covers Barth's career chronologically, providing insight into his theological development as it relates to Scripture."--Back cover
Includes bibliographical references and indexes
Keywords: Barth, Karl, -- 1886-1968; Bible -- Criticism, interpretation, etc; Theology, Doctrinal